Entrepreneurship challenges: the case of Jordanian start-ups - Mohammad Alawamleh; Yara Hanna Francis; Kamal Jamal Alawamleh (Journal of Innovation and Entrepreneurship, 2023)
Abstract This study investigates challenges facing entrepreneurs in Jordan, identifies some of problems specific to SMEs, and offers some solutions to help these companies improve their conditions. This study collected primary data through interviews with entrepreneurs in four start-up companies specialized in diverse fields, including information technology, consulting, training, and e-marketing. This study found many obstacles facing entrepreneurs in Jordan, the most important of which are financial and logistical support, the challenge of distributing work, owning operating experiences, obtaining information, commercial relations, and networking. The results of this study showed that women face greater challenges in relation to financing and investment opportunities. Finally, this study proposes some solutions which expected to be applied to improve the business environment, the most important of which is that the Jordanian Ministry of Digital Economy and Entrepreneurship should activate pilot projects and stimulate investment in them, facilitating the development and deployment of technical knowledge in private sector development.